Moderate plant water stress reduces fruit drop of "Rojo Brillante" persimmon (Diospyros kaki) in a Mediterranean climate - Badal, Eduardo; Abd El-Mageed, T. A.; Buesa, Ignacio; Guerra, Diego; Bonet, Luis; Intrigliolo, Diego S. (2017)
Spring fruit drop is a crucial determinant for yield in persimmon trees. Several environmental and tree endogenous factors can determine the magnitude of this physiological phenomenon. In this sense, plant water status might play a pivotal role in persimmon fruit drop occurring during spring. The main purpose of this study was to establish and quantify the effects of plant water stress on fruit drop of the ‘Rojo Brillante’ persimmon cultivar. To achieve this goal, a field experiment was conducted during three consecutive seasons with mature trees. Three irrigation regimes were tested: Control, always well watered; and two deficit irrigation (DI) treatments where water was applied at 50% of the Control regime during May and June (DIearly) or during July and August (DIlate). Plant water stress was monitored by means of midday stem water potential (Ψstem) readings. The seasonal variation of fruit drop was quantified during the entire fruit abscission period. Both DI regimes led to lower fruit drop than the Control (31 and 12% lower fruit drop for DIearly and DIlate, respectively). In addition, in the last two experimental seasons, there was a highly significant relationship between the amount of fruit that dropped during the physiological fruit drop and the average Ψstem for the period of water restrictions. However, the timing of water stress also affected the existing relationships. Early season water stress had a greater effect on reducing fruit abscission during the second wave of fruit drop. In semi-arid climates, this knowledge can be used for increasing ‘Rojo Brillante’ persimmon fruit set by restricting irrigation applications during late spring.